Application of bio-layer interferometry for the analysis of ribosome-protein interactions - Pandiarajan, Ilamathy; Walunj, Sujata B.; Banerjee, Nirjhar; Rout, Janmejaya; Srivastava, Sanjeeva; Patankar, Swati; Kaledhonkar, Sandip (Frontiers in Molecular Biosciences, 2024)
The ribosome, a ribonucleoprotein complex, performs the function of protein translation. While ribosomal RNA catalyzes polypeptide formation, several proteins assist the ribosome throughout the translation process. Studying the biochemical and kinetic properties of these proteins interacting with the ribosome is vital for elucidating their roles. Various techniques, such as zonal centrifugation, pull-down assays, dynamic light scattering (DLS), fluorescence polarization, and surface plasmon resonance (SPR) are employed for this purpose, each presenting unique advantages and limitations. We add to the repertoire of techniques by using Bio-Layer Interferometry (BLI) to examine interactions between the ribosome and translation factors. Our findings demonstrate that BLI can detect interactions of Escherichia coli ribosomes with two proteins: E. coli initiation factor 2 (IF2) and P. falciparum translation enhancing factor (PTEF). A protein (Green Fluorescent Protein; GFP) known not to bind to E. coli ribosomes, shows no binding in the BLI assay. We show that BLI could be used to study the ribosome-protein interactions as it has key advantages like label-free procedures, ease of assay performance, and ribosome sample reuse. Our results highlight the comprehensive use of BLI in studying the ribosome-protein interactions, in addition to studying protein-protein and protein-ligand interactions.